Precisiones de enseñanza para Speaking y su influencia en el aprendizaje del idioma inglés de los estudiantes de educación básica superior de la unidad educativa “Enrique Ponce Luque” cantón Quevedo - Botto Morán, María Marisol (2016)
The development of this research reflects the analysis INFORMATION TEACHING SPEAKING AND ITS INFLUENCE IN LEARNING ENGLISH LANGUAGE STUDENTS OF HIGHER EDUCATION BASIC EDUCATION UNIT "ENRIQUE PONCE LUQUE" CANTON QUEVEDO which reflects the relationship between these two variables and their effect on the school's academic development of students. For the study of the main theories defined the technique SPEAKING, their types, levels of learning and the evaluative scale highlighting the educational system of English in high school, in addition to the meaning of the English language with the application of methodologies according grammatical proficiency levels to develop in the academic stage. For the analysis of survey results previously teachers, students applied from a simple random probability sampling NO, in order to obtain concrete data on the phenomenon investigated. Finally, the results raised by the conclusions and recommendations which generated the implementation of a training plan for teaching basic SPEAKING, teaching techniques of the research institution.